Technology as an ally to fight COVID-19 - Tarazona Reyes, Abel José (2020)
The infectious disease COVID-19, or commonly called coronavirus disease, has put the whole world on alert and even more so now that the World Health Organization (WHO) has declared it a pandemic. Worldwide, countries are looking for a cure and applying new ways of prevention to flatten the curve of those infected, so both the area of medicine and the area of technology are doing their best to find effective solutions to this pandemic. The fields of artificial intelligence and big data, seek to contribute technologically using the existing information of the citizens and of which it is possible to have confidence, in which many of these services will have a purpose with impact, since they have had exponential advances in the last decades.